2020
DOI: 10.1186/s43054-020-00023-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of late preterm newborns in Upper Egypt

Abstract: Background: The incidence of preterm births is increasing and has become a global health concern. This study aimed to compare the outcome of late preterm (LPT) to full term (FT) neonates at two large hospitals in Upper Egypt. Results: Out of 250 newborns included in the study, 180 (72%) were FT and 70 (28%) were LPT. More than half of the LPT newborns (52.9%) were admitted to the neonatal intensive care unit (NICU), compared with 26.7% of FT newborns. Delivery of LPT was associated with an increased risk of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
(61 reference statements)
2
14
0
Order By: Relevance
“…Although PPROM is an indication for NICU admission in our hospital protocol, it should be clarified that our local policy is to admit all infants delivered after PPROM to the NICU for observation immediately after delivery and to be discharged after 48 h if they meet the discharge criteria. The overall rate of NICU admission among the LPIs included in our cohort was 56% which is quite similar to the rate reported from USA (56%) (25) and from Egypt (53%) (26), a nearby Arab country, compared with 30% in Turkey (27). In a previous report, we found that maternal PPROM was the major indication of NICU admission among term infants (28).…”
Section: Discussionsupporting
confidence: 87%
“…Although PPROM is an indication for NICU admission in our hospital protocol, it should be clarified that our local policy is to admit all infants delivered after PPROM to the NICU for observation immediately after delivery and to be discharged after 48 h if they meet the discharge criteria. The overall rate of NICU admission among the LPIs included in our cohort was 56% which is quite similar to the rate reported from USA (56%) (25) and from Egypt (53%) (26), a nearby Arab country, compared with 30% in Turkey (27). In a previous report, we found that maternal PPROM was the major indication of NICU admission among term infants (28).…”
Section: Discussionsupporting
confidence: 87%
“…A study by Lavanya et al had shown a similar higher incidence of significant hyperbilirubinemia (57.0%) among the late preterm neonates. 12 Similarly, the incidence of significant jaundice was 59% in a study by Bansal et al and also with other studies by Aziz et al and Algameel et al 14,17,19 Our study showed that significant hyperbilirubinemia was higher among the male child when compared to the female child (74.2% versus 47.1%) and it was found to be statistically significant (p=0.007), which is consistent to the study results of Gupta et al, where the study had reported that males were found to have significantly higher incidence of jaundice when compared to the females among the late preterm group; similar association had been reported by studies conducted elsewhere. 13,21,22 A study by Bansal et al along with other studies have failed to show such association.…”
Section: Resultssupporting
confidence: 60%
“…14,52,59 A study by Lavanya et al showed that large for gestation, gestational age, birth trauma and previous sibling with severe jaundice are the clinical variables significantly associated with significant jaundice. 12 11,14,17,24 A study by Bhutani et al also have concluded that large for gestational age and late preterm infants disproportionately developed kernicterus as compared with those who were appropriate for gestational age and term. 15 In a study by Aynalem et al, Rh incompatibility (p=0.002), ABO incompatibility, perinatal asphyxia and sepsis were significantly associated with hyperbilirubinemia.…”
Section: Resultsmentioning
confidence: 99%
“…Rates of PTB were 9.6% (n = 84) at less than 37 weeks and 4.5% (n = 43) at less than 34 weeks of pregnancy in a previous study, 10 but our findings were similar to previously reported results in Egypt (28%). 15 Different rates were attributed to the different sample size in both studies. Besides, our data represent PTB rates before the 37th week of pregnancy.…”
Section: Discussionmentioning
confidence: 97%